PENGARUH JUS BELIMBING MANIS (Averrhoa Carambola) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - nonce nova legi; Grace K.L. Langi; Fred Rumagit; Ana B Montol; Feyske Arunde (POLTEKKES KEMENKES MANADO, 2020)
Hypertension is a condition when the condition of the blood in the blood vessels increases chronically. This happens because the heart works harder to pump blood to meet the body's oxygen and nutritional needs. The purpose of this study was to determine the effect of sweet starfruit juice (Averrhoa carambola) on blood pressure reduction in hypertensive patients. Using a literature review research method through a journal review on the effect of giving sweet starfruit juice (Averrhoa carambola) on blood pressure in patients with hypertension. Article searches are accessed from Google Scholar data. This narrative literature review was carried out on several research articles and literature review articles published in the last ten years. From the results of the data search conducted through this literature review, there are six sources of data obtained which are related to the effect of giving sweet starfruit juice (Averrhoa carambola) on blood pressure in hypertensive patients. From giving sweet starfruit juice to hypertensive patients, many have resulted in a decrease in blood pressure after giving sweet starfruit juice to hypertensive patients. Of the six data sources reviewed, there was a decrease in blood pressure after giving starfruit juice to hypertensive patients. Giving star fruit juice is a simple way that can help reduce the risk of hypertension.